Effect of FGFR alteration on prognosis in 1963 urothelial carcinoma patients with immune checkpoint inhibitors: Implying combination of FGFR inhibitor and immunotherapy for FGFR-altered urothelial carcinoma - Yuxuan Song; Shan Jiang; Yun Peng; Caipeng Qin; Yiqing Du; Tao Xu (Elsevier, 2024)
Immune checkpoint inhibitors (ICIs) are essential for urothelial carcinoma (UC) treatment. Fibroblast growth factor receptor (FGFR) alterations, as common oncogenic drivers in UC, have been reported to drive T cell depletion of UC immune microenvironment via up-regulating FGFR signaling, which indicated FGFR alterations potentially result in reduced response to ICIs. In addition, the selective pan-FGFR inhibitor showed better clinical benefit in clinical trials, indicating FGFR has emerged as critical therapeutic target via inhibiting FGFR signaling. The present study aims to evaluate prognosis and response to ICIs between FGFR-altered UC patients and FGFR-wildtype UC patients via 1963 UC patients and offers new insights into personalized precision therapy and combination therapy for UC.